A study of serum magnesium level in type 2 diabetes mellitus and its significance - G, Prabhu; AM, Radha; S, Balasubramaniyan (International Journal of Medical Research and Review, 2015)
Introduction: Hypomagnesaemia has been reported to occur in 25-38% of patients with Type 2 DM especially in those without good metabolic control. This present study has been undertaken to estimate serum magnesium level of patients with diabetes mellitus and to correlate between serum magnesium levels and glycemic control, duration of diabetes and its complications. Methods and Materials: This is a prospective study done in March 2015 in Rajah Muthiah Medical College and Hospital. 132 Type 2 DM patients included in the study was estimated with serum magnesium level and compared with the age matched control group. Results: The mean serum magnesium was 1.74+ 0.32mg/dl. Of the patients, 33(25%) had low serum magnesium levels (less than or equal to 1.5mg/dl). We observed that serum magnesium levels were lower in patients with increasing duration of diabetes. Out of the 19 patients who had hypomagnesaemia, 18 patients had HbA1c > 7 %. This correlates between hypomagnesaemia and poor glycemic control in our study. Conclusion: Serum magnesium level was low in Type 2 DM; serum magnesium was low in patient with poor glycemic control.